2009
DOI: 10.1021/jp900281h
|View full text |Cite
|
Sign up to set email alerts
|

Density Functional Theory Study of the CO Insertion Mechanism for Fischer−Tropsch Synthesis over Co Catalysts

Abstract: Different mechanisms have been proposed for Fischer-Tropsch synthesis, the conversion of CO and H 2 to long-chain alkanes. Density functional theory calculations indicate that CO activation has a barrier of 220 kJ/mol on Co(0001), and hence the concentration of surface C or CH 2 species is likely too low to explain the high chain growth probability. Hydrogenation lowers the C-O dissociation barrier to 90 kJ/mol for HCO and to 68 kJ/mol for H 2 CO; however, CO hydrogenation has a high energy barrier of 146 kJ/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

32
187
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 161 publications
(219 citation statements)
references
References 50 publications
32
187
0
Order By: Relevance
“…Inderwildi et al found the same pathway via HCO and CH 2 O molecules, which undergo a lower barrier of 0.85 eV for C-O bond cleavage of CH 2 O [131]. Besides, the similar results of C-O bond cleavage (0.93 eV via HCO and 0.70 eV via CH 2 O) were obtained by Saeys and coworkers [114]. Moreover, Iglesia and coworkers Fig.…”
Section: Co Activationsupporting
confidence: 54%
See 4 more Smart Citations
“…Inderwildi et al found the same pathway via HCO and CH 2 O molecules, which undergo a lower barrier of 0.85 eV for C-O bond cleavage of CH 2 O [131]. Besides, the similar results of C-O bond cleavage (0.93 eV via HCO and 0.70 eV via CH 2 O) were obtained by Saeys and coworkers [114]. Moreover, Iglesia and coworkers Fig.…”
Section: Co Activationsupporting
confidence: 54%
“…PBE functional [124] or PW functional [123]), and other parameters were employed in these calculations. Despite this fact, similar trends can be observed Understanding of Co-Based F-T Catalysis 147 PBE functional, PAW pseudopotential in VASP package were employed [114,117], and the data in parentheses are calculated on Co (0001) with 1/3 ML CO coverage [117]. Perdew-Burke-Ernzerhor form (PBE) of generalized gradient corrections and Troullier-Martins norm-conserving scalar relativistic pesudopotential in SIESTA package were employed [116,120,121].…”
Section: Adsorption Energies Of the Surface Speciesmentioning
confidence: 59%
See 3 more Smart Citations